Guide to laboratory establishment for plant nutrient analysis - Motsara, M.R (Food and Agriculture Organization of the United Nations, 2008)
This publication provides practical guidelines on establishing service laboratories for the analysis of soil, plants, water and fertilizers (mineral, organic and biofertilizers).